IMPLEMENTASI METODE PEMBIASAAN BERBASIS TEORI BEHAVIORISTIK DALAM MEMBINA KEDISIPLINAN SISWA DI RA TUNAS LITERASI QUR’AN CURUP UTARA - Oktia Anisa Putri; Sutarto Sutarto (INCARE, International Journal of Educational Resources, 2023)
One of the methods applied to instill discipline in early childhood is the habituation method. This method is a method based on behavioristic theory. The importance of discipline is instilled in children from an early age because it will affect the character and personality of children when they grow up. So that discipline must be instilled from a young age to prevent the destruction of future generations. The purpose of this study was to determine the implementation of the Behavioristic Theory-based habituation method in fostering student discipline at RA Tunas Qur'ani Literacy Curup Utara. This study uses a qualitative method with a descriptive approach. This study aims to describe the implementation of rewards in shaping the disciplinary character of young children. The technique of collecting research notes is structured interviews, non-participant observation, and documentation. This research uses a type of field research, which is a type of research where data collection is carried out in the field. There are two kinds of data sources, namely primary and secondary data sources. There are three data collection techniques used, namely observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and data verification. While the technique of testing the validity of the data using triangulation techniques. The results of the research on the application of behavioristic theory-based habituation methods at RA Tunas Literacy Quranic Curup Utara are seen as effective in instilling Islamic values. It has been proven not only in class, but has been done through habituation when students are about to take ablution getting used to queuing, when children come to school they also don't forget to shake hands and greet the teacher greeting each other, taking turns, getting used to queuing culture, and other habits.